Nummulites and calcareous nannofossils from Lower Eocene beds in the area of Veliko Târnovo (North Bulgaria) - Aladžova-Hriščeva, Kina; Pavšič, Jernej (Geologija, 1988)
From two sections in the Veliko Târnovo area nummulites and calcareous nannofossils were studied. In the Šemševo section by comparison with nummulites the nannoplankton biozone NP 13, and in the Balvan section biozones NP 9 and NP 11 were separated.